Genomics, Proteomics, and the Nervous System - Clelland, James D.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
The potential for malfunction of this large number of complex biological systems is great, leading to the many behavioral and cognitive deficits observed in human psychiatric and neurological disorders. Genomics, Proteomics, and the Nervous System discusses research designed to increase our understanding of the nervous system and its structures and activities. This volume of Advances in Neurobiology discusses the utilization of genomic and proteomic technologies, to address facets of neurobiology including development and epigenetic regulation, functions in learning and memory, and changes associated with neurological and psychiatric disorders.
Development -- The Genomics of Turner Syndrome and Sex-biased Neuropsychiatric Disorders -- Mental Retardation and Human Chromosome 21 Gene Overdosage: From Functional Genomics and Molecular Mechanisms towards Prevention and Treatment of the Neuropathogenesis of Down Syndrome -- Epigenetic programming of stress responses and trans-generational inheritance through natural variations in maternal care -- Prenatal Viral Infection in Mouse: an Animal Model of Schizophrenia -- Proteomic actions of growth hormone in the nervous system -- - Learning and Memory -- Gene expression and signal transduction cascades mediating estrogen effects on memory -- Diagnostic genome profiling in mental retardation -- Genomic Imprinting and Sexual Experience-Dependent Learning in the Mouse -- Proteomic Analysis of the Postsynaptic Density -- - Behavior -- Functional Genomic Dissection of Speech and Language Disorders -- Studying Human Circadian Behavior Using Peripheral Cells -- Genome-wide expression profiles of amygdala and hippocampus in mice after fear conditioning -- - Psychiatric Disorders -- Genetic Studies of Schizophrenia -- Proteomics of the Anterior Cingulate Cortex in Schizophrenia -- Proteome Effects Of Antidepressant Medications -- - Neurological Disorders -- MicroRNAs in Neurodegenerative Disorders -- Specific and surrogate cerebrospinal fluid markers in Creutzfeldt-Jakob disease -- Genome-Wide Expression Studies In Autism-Spectrum Disorders: Moving From Neurodevelopment To Neuroimmunology -- Protein expression profile of Alzheimer$1 (Bs disease mouse model generated by Difference Gel Electrophoresis (DIGE) approach -- Proteomic Analysis of CNS Injury and Recovery -- Maldi Imaging Of Formalin-Fixed Paraffin-Embedded Tissues: Application To Model Animals Of Parkinson Disease For Biomarker Hunting -- Comparative Proteomic Analysis as a method to investigate Inflammatory and Neuropathic Pain.s
Keywords: Medicine; Neurosciences; Biomedicine; Neurosciences